Jerks at work toxic coworkers and what to do about them - West, Tessa (New York Penguin, 2021)
From open floor plans and Zoom calls to Slack channels, the workplace has changed a lot over the years. But there?s one thing that never changes: you?ll always encounter jerks. Jerks at Work is the definitive guide to dealing with?and ultimately breaking free from?the overbearing bosses, irritating coworkers, and all-around difficult people who make work and life miserable.
Includes bibliographical references and index.
Keywords: Psychology, Industrial